Corpo organico, corpo animale : le rêverie bachelardiane della corporeità - Dal Pozzolo, Marco (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
In Bachelard’s work, at the crossroads between the poetics of the elements and poetics of dwelling, profound insights into corporeality emerge, articulated to space and environment. On the one hand, Bachelard thematizes the relationship that humans have with their body, both as a foundamental structure of experience and as organic matter. On the other hand, he addresses the issue of the relationship between the human body and the animal body, deepening the indistinction area between the two: the power of the imagination allows an access to experiences that are rooted in an animal relationship between body and world. The Bachelardian analysis of poetic images reveals an atypical and original contribution to the phenomenology of corporeality: this aspect is highlighted also through the analysis of the convergence with Husserl’s philosophy, and at the same time of the divergence between imagination and empathic-analogical reconstruction as ways of accessing the animal body. Keywords: Corporeality – Organic – Animalistic- Imagination – Phenomenology